ANALISIS NILAI RELIGIUSITAS DAN MAKNA DALAM TEMBANG PANGKUR SUNAN DRAJAT - Lukluk Ainiyah; Kusmiyati Kusmiyati; Haerussaleh Haerussaleh (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
The purpose of this study is to describe Paul Ricoeur's hermaneutics on Sunan Drajat song, and analyze the religious values ​​contained in sunan drajat song. This type of research is descriptive qualitative. The data analysis technique used is Hermaneutika as the paul ricoeur interpretation system and the analysis of the value of religiosity. Based on the results of the analysis, first found the analysis of the value of religiosity of human relations with God the creator of nature, From this research it can be seen that there is a value of religiosity that contains human-human relations contained in the Sunan Drajat song, and found the semantic hermaneutika analysis / symbol and reflection from Paul Reicoer as: Singo clinching which means Man and the passions; stars and the sun which means man and pleasure